Acquiring Feedback from Students in Co‐Taught Classes. Issue 3 (8th October 2019) - King‐Sears, Margaret E.; Brawand, Anne; Johnson, Todd M.
Abstract: Acquiring feedback from students with and without disabilities about their experiences in co‐taught settings can provide valuable information to co‐teachers. In this article, informal surveys, interviews, and illustrations, derived from research, are described for co‐teachers to acquire feedback from students. Examples of queries and response formats are provided. Emphasis is also on co‐teachers using students' feedback to maintain effective practices and make instructional refinements.